Does hip displacement influence health-related quality of life in children with cerebral palsy?. (December 2014) - Jung, Nikolai H.; Pereira, Barbara; Nehring, Ina; Brix, Olga; Bernius, Peter; Schroeder, Sebastian A.; Kluger, Gerhard J.; Koehler, Tillmann; Beyerlein, Andreas; Weir, Shannon; von Kries, Rüdiger; Narayanan, Unni G.; et al.
Abstract Objective: To evaluate the association of hip lateralisation with health-related quality of life (HRQL) in children with cerebral palsy (CP) using the Caregiver Priorities and Child Health Index of Life with Disabilities (CPCHILD®) questionnaire. Methods: We assessed n = 34 patients (mean age: 10.2 years, SD: 4.7 years; female: n = 16) with bilateral CP and Gross Motor Function Classification System (GMFCS) Level III–V using the CPCHILD® questionnaire. Hip lateralisation was measured by Reimer`s migration percentage (MP). Results: There was an association between both, MP and GMFCS with CPCHILD® total score. Stratified analyses did not suggest interaction of the association between MP and CPCHILD® total score by GMFCS level. After adjustment for GMFCS level, we found a significant linear decrease of CPCHILD® total score of −0.188 points by 1% increment in MP. Conclusions: There was an association between MP and HRQL, which could not be explained by the GMFCS level.